Tracing the Flow and Figures of Classical Islamic Historiography - Siska Anggrianto (Tarikhuna: Journal of History and History Education, 2025)
This study examines the development of classical Islamic historiography through five main schools: the Yemeni, Medinan, Iraqi, Syrian, and Persian schools. The aim of this study is to identify the characteristics, historiographical approaches, and contributions of each school to the formation of Islamic civilization’s history. This study uses a qualitative approach and historical research methods, employing critical analysis of library sources through four main stages: heuristics, collecting primary and secondary sources, such as classical texts, historical chronicles, and modern scientific works. Next, source criticism includes evaluating the authenticity and credibility of the source. Interpretation involves analyzing the meaning and socio-cultural context of each data. Historiography is the systematic arrangement of the interpretation results into a narrative. The results of this study indicate that each school possesses distinct characteristics. The Yemeni school emphasizes mythological and prophetic stories. The Medinan school focuses on the verification of sanad (chain of transmission) and the hadith methodology. The Iraqi school developed political and chronological history writing. The Syrian school was influenced by Umayyad rule and the Arab spirit, while the Persian school introduced rationality and administrative systematics in historiography. This research contributes to strengthening the methodology of classical Islamic historiography by clarifying source analysis techniques and data validity criteria often overlooked in previous research. Furthermore, it broadens the understanding of the early Muslim intellectual tradition that shaped a paradigm of historical writing influential up to the modern era.